Perspectives of choice and control in daily life for people following brain injury: A qualitative systematic review and meta‐synthesis. (31st October 2022) - Murray, Carolyn M.; Weeks, Scott; van Kessel, Gisela; Guerin, Michelle; Watkins, Emma; Mackintosh, Shylie; Fryer, Caroline; Hillier, Susan; Stanley, Mandy
Abstract: Background and Objective: Acquired brain injury (ABI) can result in considerable life changes. Having choice and control over daily life is valued by people following ABI. This meta‐synthesis will analyse and integrate international research exploring perspectives of choice and control in daily life following ABI. Methods: Databases were searched from 1980 to 13 January 2022 for eligible qualitative studies. After duplicates were removed, 22, 768 studies were screened by title and abstract, and 241 studies received full‐text assessment with 56 studies included after pearling. Study characteristics and findings were extracted that related to personal perspectives on choice and control by people with an ABI (including author interpretation and quotes). Data from each study were coded and then segments of coded data across the studies were compared to create multiple broad categories. Findings: Findings were then reduced from categories into 3 overarching themes with 12 subthemes. These themes were: (1) feeling like a second‐class citizen; (2) reordering life and (3) choosing a path. Participants with an ABI tussled between their feelings of loss following brain injury and their thinking about how they start to regain control and become agents of their own choices. The themes describe their sense of self, their changed self and their empowered self in relation to 'choice and control'. Conclusions: Re‐engaging with choice and control after ABI is dynamic and can be challenging. Health professionals and supporters need to facilitate a gradual and negotiated return to agency for people following ABI. A sensitive and person‐centred approach is needed that considers the readiness of the person with ABI to reclaim choice and control at each stage of their recovery. Clear service or process indicators that are built on lived experience research are needed to facilitate changes in service delivery that are collaborative and inclusive. Patient or Public Contribution: This review included the voices of 765 people living with ABI and was conducted by a diverse team of allied health professionals with practice knowledge and research experience with people following ABI. Twenty‐nine of the 56 included studies had participants contributing to their design or analysis.